Patient-reported fatigue and its impact on patients with systemic lupus erythematosus. (February 2014) - Sterling, KL; Gallop, K; Swinburn, P; Flood, E; French, A; Sawah, S Al; Iikuni, N; Naegeli, AN; Nixon, A
Fatigue is a hallmark symptom of systemic lupus erythematosus (SLE), often associated with flares, side effects of treatment, and extensive organ damage and may have a significant impact on health-related quality of life (HrQoL). To date, the experience of fatigue in patients with SLE is underexplored. This study explored the experience of fatigue in patients with SLE and its impact on their lives through qualitative interviews. This cross-sectional qualitative study was conducted with 22 adult patients with SLE, recruited from two clinical sites in the United States. In-person semi-structured interviews were conducted and thematic analysis was performed focusing on the experience of fatigue in SLE. Results indicated that 21 out of 22 patients experienced fatigue due to SLE. Patients reported that fatigue was variable in nature in terms of both severity and frequency. Fatigue was described as having an impact on multiple aspects of a patient's life: emotions, cognition, work, activities of daily living, leisure activities, social activities, and family activities. Understanding how patients with SLE describe the symptom of fatigue and how it impacts their lives is the key to better understanding how to measure fatigue in clinical studies evaluating new treatments for SLE.